Long-Term Efficacy and Safety of Upadacitinib in Patients with Rheumatoid Arthritis: Final Results from the BALANCE-EXTEND Open-Label Extension Study - Alan Kivitz; Alvin F. Wells; Juan I. Vargas; Herbert S. B. Baraf; Maureen Rischmueller; Justin Klaff; Nasser Khan; Yihan Li; Kyle Carter; Alan Friedman; Patrick Durez (Rheumatology and Therapy, 2023)
Abstract Introduction Upadacitinib (UPA) is an oral, selective Janus kinase inhibitor that has demonstrated favorable efficacy with an acceptable safety profile across a global, phase 3 program in rheumatoid arthritis (RA). This phase 2 open-label extension investigated the efficacy and safety of UPA through 6 years of treatment. Methods Patients from two phase 2b trials (BALANCE-1 and -2) enrolled in BALANCE-EXTEND (NCT02049138) and received open-label UPA 6 mg twice daily (BID). Dose increases to 12 mg BID were required for patients with < 20% improvement in swollen or tender joint counts at weeks 6 or 12 and permitted for those not achieving Clinical Disease Activity Index (CDAI) low disease activity (LDA; CDAI 2.8 to ≤ 10). Dose reduction to UPA 6 mg BID was permitted only for safety or tolerability reasons. After January 2017, the 6/12 mg BID doses were replaced by 15/30 mg once-daily extended-release equivalents. Efficacy and safety were monitored up to 6 years of UPA treatment; outcomes included rates of achievement of LDA or remission. Data were analyzed for patients who received the lower UPA dose throughout; titrated up to the higher UPA dose from weeks 6 or 12; or titrated to the higher UPA dose and back down. Results Overall, 493 patients entered BALANCE-EXTEND (‘Never titrated’, n = 306; ‘Titrated up’, n = 149; ‘Titrated up and down’, n = 38), and 223 patients (45%) completed the 6-year study. Total cumulative exposure was 1863 patient-years. Rates of LDA and remission were maintained through 6 years. Overall, 87%/70%/73% of patients in the ‘Never titrated’/‘Titrated up’/‘Titrated up and down’ groups achieved CDAI LDA at week 312, while the respective rates of Disease Activity Score 28 with C-reactive protein meeting LDA and remission criteria were 85%/69%/70% and 72%/46%/63%. Improvements in patient-reported outcomes were similar among the three groups. No new safety signals were identified. Conclusions In this open-label extension of two phase 2 studies, UPA demonstrated sustained efficacy and an acceptable safety profile through 6 years of treatment in patients who completed the study. These data support a favorable long-term benefit–risk profile of UPA in patients with RA. Trial Registration Trial registration number: NCT02049138.